"The woman in the background": Gendered Nouns in CNN and FOX Media Discourse. (September 2020) - Konnelly, Lex
Linguistic democratization, the goal or practice of increasing social equity through language, has not figured prominently in corpus studies. However, corpus-based approaches present the opportunity to probe questions of unequal linguistic representation on a large scale, providing crucial insights into how actors are classified in public discourse, especially with respect to the representation of gender relations and inequity. This paper draws on corpus methods to analyze the patterning of two generic, gendered nouns— woman and man —in American news television discourse. Results of both quantitative and qualitative analyses show that patterns for both grammatical factors (syntactic function, determiner type, pre-modification) and collocational behavior are largely consistent across networks, suggesting that gender ideologies expressed by newscasters and talk show hosts on both networks are not substantially different from one another. This study shows how elements of discourse that may be considered innocuous and below the level of consciousness—such as the position of certain nouns in the sentence, the determiners that specify them, and the adjectives that modify them—can provide valuable diagnostics of discourse-level democratization, and reveal deeper sociocultural ideologies about gendered individuals that are regularly perpetuated in public news discourse, regardless of the networks' own political positioning.